Clinical characterization of a novel episodic ataxia in young working Cocker Spaniels - Clara Sarró; Catherine Stalin; Rodrigo Gutierrez‐Quintana; Ana Cloquell (Journal of Veterinary Internal Medicine)
Abstract Background Episodic ataxias (EAs) are a rare group of paroxysmal movement disorders (PMD) described in human medicine with only one suspected case described in veterinary literature. Hypothesis/Objectives This study aimed to provide clinical description of a suspected primary EA in working Cocker Spaniel (WCS) dogs. Animals Seven WCS dogs with suspected primary EA. Methods Descriptive, retrospecitve, multicenter study. Clinical signs, video footage, investigations, treatment, and outcome were reviewed. Owners of affected dogs were invited to complete a questionnaire. Results The mean age at clinical onset was 4 months. Signs were acute and included episodic body swaying, titubation, cerebellar ataxia, wide‐base stance, and hypermetria, all while mentation remained unaltered. Neither autonomic nor vestibular signs nor hyperkinetic movements were observed. Duration of episodes ranged from 30 minutes up to 24 hours, and their frequency varied from weekly to once every 5 months. When investigations were performed, results revealed no abnormalities except for 1 dog that had increased gluten antibody titers. None of the dogs deteriorated, and in dogs with available follow‐up (5/7) the frequency of episodes decreased or completely resolved, from which the majority (4/5) received gluten‐free diet. Conclusion and Clinical Importance A novel PMD was identified in young WCS, manifesting as EA. The condition is suspected to have a primary (genetic) etiology, although the cause of this manifestation has not yet been identified. Episodic ataxia in our WCS had a good prognosis. Veterinarians must be aware of this presentation, and further investigations are needed to determine the origin of the clinical signs.